Sosialisasi Potensi Bioetanol Berbasis Jagung sebagai Upaya Peningkatan Nilai Tambah Komoditas Lokal Desa Sambelia - I Ketut Wiryajati; Lalu Gema Baruna Pandu Suhendra; Pipit Haryati; Weni Sumanisa; Dhira Diana Agustina (Universitas Mataram, 2026)
This community service activity assesses the potential of corn residue as a lignocellulosic feedstock for bioethanol production in Sambelia Village, Indonesia, using a scenario-based analytical approach. Field surveys and interviews with local stakeholders indicate that approximately 100 hectares of corn farmland generate about 800 tons of corn residues annually, mainly consisting of stalks and cobs. In the absence of laboratory data on moisture content and carbohydrate composition, realistic technical assumptions were applied to represent practical field conditions. Three scenarios—conservative, moderate, and optimistic were formulated to reflect variations in effective carbohydrate fraction and the efficiencies of hydrolysis and fermentation processes. The analysis indicates that potential bioethanol production ranges from approximately 81,600 L/year (816 L/ha) under conservative conditions to 205,200 L/year (2,052 L/ha) under optimistic conditions, with the moderate scenario yielding around 138,700 L/year (1,387 L/ha). From an energy perspective, these outputs correspond to 1,722–4,329 GJ per year (0.48–1.20 GWh), demonstrating a meaningful contribution to local renewable energy supply. This scenario-based method provides a flexible and realistic framework for early-stage planning of village-scale bioethanol development, particularly in community service programs where detailed laboratory data are limited. Overall, the activity highlights the importance of biomass quality, residue availability, and technological efficiency in supporting waste valorization, rural energy resilience, and sustainable energy transition.